An overview of the secondary structure of the V4 region of eukaryotic small-subunit ribosomal RNA. - Nickrent, D L (1991)
The V4 region of the small subunit (18S) ribosomal RNA was examined in 72 different sequences representing a broad sample eukaryotic diversity. This domain is the most variable region of the 18S rRNA molecule and ranges in length from ca. 230 to over 500 bases. Based upon comparative analysis, secondary structural models were constructed for all sequences and the resulting generalized model shows that most organisms possess seven helices for this region. The protists and two insects show from one to as many as four helices in addition to the above seven. In this report, we summarize secondary structure information presented elsewhere for the V4 region, describe the general features for helical and apical regions, and identify signature sequences useful in helix identification. Our model generally agrees with other current concepts; however, we propose modifications or alternative structures for the start of the V4 region, the large protist inserts, and the sector that may possibly contain a pseudoknot.